PETSOFT (CIPEEX, 2025)
PetSoft is a project entirely focused on animal adoption and donations. It connects users who wish to adopt any kind of animal with those offering them. The platform allows both institutions and individual users to list animals for adoption and includes a donation section where users can contribute to partner institutions associated with PetSoft. The project aims to streamline the adoption process and support animal welfare through its donation features.
Keywords: adoption; donation; animal